A letter to Agnes McCausland Richardson Etherington (1880-1854). (1st December 2021) - Klassen, Lois
"Dear Agnes" is a fictitious correspondence that I shared with Agnes McCausland Richardson Etherington (1880‐1954) during my doctoral studies in the Cultural Studies Program at Queen's University (2014-2019). Agnes Etherington is a key figure in the development of fine arts programs at Queen's, including its art collection. Owing to her bequest of the Etherington House, the university's art facility bears her name. The entire correspondence that we shared, and that was inserted as textual interruptions into my final dissertation portfolio, includes personal photos and a genealogy that chronologically records activities of Indigenous resurgence that occurred during my studies. What follows is an excerpt of the correspondence. This text is based on one of the four letters found in the portfolio.